Investigating the pre- and post-COVID-19 vaccination infection status of Iranian dental students: a cross-sectional study - Fatemeh Owlia; Mohammad-Javad Kargar; Maryam Kazemipoor (The Egyptian Journal of Bronchology)
Abstract Background Dental students face a potential risk of COVID-19 exposure due to close patient contact and aerosol-generating procedures. This study explores the frequency of COVID-19 infection among Iranian dental students in 2022 following different vaccination doses. Methods A cross-sectional study was used to collect self-reported COVID-19 status. A total of 261 dental students volunteered to participate in the study. A total of 252 valid forms were gathered, with a response rate of 96.55%. Data analysis was performed using descriptive statistics, mean and standard deviation, and chi-square and Fisher exact tests by Spss17 (Chicago, USA) software. Results The rate of COVID-19 infection significantly decreased after the first and third doses of vaccination. The rate of COVID-19 infection was not very different after the first, second, and third doses of the vaccine according to the type of vaccine. Despite no significant difference in COVID-19 infection rates between genders, study years, or vaccine types (excluding AstraZeneca), participants who received the AstraZeneca vaccine experienced more serious side effects compared to those who received other vaccines. Conclusion Vaccination appeared to reduce the rate of COVID-19 infection among dental students and may have decreased the duration of infection following different vaccine doses. There was no significant difference in infection rates based on the type of vaccine received. Further research is needed to investigate the potential side effects and long-term effectiveness of COVID-19 vaccines.